Relationship Between ASA Scores and 30-Day Readmissions in Patients Undergoing Anterior Cervical Discectomy and Fusion - Phan, Kevin; Kim, Jun S; Lee, Nathan J; Kothari, Parth; Cho, Samuel K (Spine (Philadelphia, Pa. 1976), 2017)
Retrospective study of prospectively collected data. To assess the American Society of Anesthesiologists (ASA)score as an independent predictor of 30-readmissions after anterior cervical discectomy and fusion (ACDF). The ASA classification scheme was introduced in 1941 to establish a scoring system to evaluate the overall health status and comorbidities of patients before surgery10-12. Although the score was designed to predict postoperative complications, it may also be used as a predictor of perioperative risk. Data collected for the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database in the period 2005 to 2012 were used in the present analysis. Current Procedural Terminology codes were used to identify elective ACDF cases (CPT codes: 22551, 22554, and 63075). The primary study outcome was 30-day readmission rates after elective ACDF in adults. Univariate and multivariate analysis was used to determine whether any of age, sex, race, body mass index, comorbidities, operative variables, or ASA class were predictors of 30-day readmission rates after ACDF. From the ACS-NSQIP database, 1701 elective ACDF cases were included for analysis, including 92 (5.5%) ASA class 1,955 (56.1%) ASA class 2,618 (36.3%) ASA class 3 and 34 (2.0%) ASA class 4 patients. Using ASA class 1 as a reference, significant independent predictors included being in ASA class 4 [odds ratio (OR) 5.7; 95% confidence interval (CI) 0.58-56.7; P = 0.039], having cardiac comorbidities (OR 2.2; 95% CI 1.2-4.2; P = 0.017), and prior strokes (OR 3.8; 95% CI 1.4-10.1; P = 0.0086). In conclusion, the unplanned readmission rate for patients undergoing ACDF was 3.2%. There was a significant and independent association between a high ASA class (class 4), cardiac comorbidities and prior strokes with 30-day unplanned readmissions after ACDF. The ASA score may be a valuable tool for the preoperative assessment of ACDF patients for risk of unplanned readmissions. 3.